Training and Mentoring on the Use of E-Books Based on the Professional Flip PDF Application as Digital Teaching Materials for Physical Education, Sports and Health Teachers in the Independent Learning Curriculum in Palembang City - Aryanti, Silvi; Hartati; Destriana; Fitri Agung Nanda; Samsul Azhar; Frayesi (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
This community service activity is to conduct training and mentoring in the use of E-Books Based on the Flip PDF Professional Application as digital teaching materials. This community service activity is in collaboration with partners, namely Subject Teachers' Conference Physical education, sports and health teachers in Palembang City. The target audience in this community service activity in Palembang City. The method of implementing the activity is by mentoring Physical education, sports and health teachers in Palembang City in using the E-Book Flip PDF Professional. The stages in community service activities are the preparation stage, the implementation stage and the evaluation stage. The results of this community service activity are the pretest results, namely 10%. Physical education, sports and health teachers in Palembang City do not yet know about the operation of the E-Book Flip PDF Professional, namely 10%. According to Physical education, sports and health Teachers, the use of E-Book Flip PDF is less effective, as seen from the results, namely 35%. The post-test results showed an increase in the realm of knowledge about the E-Book Flip PDF Professional, namely 90%. Physical education, sports and health teachers in Palembang City can operate the E-Book Flip PDF Professional, namely 90%. According to Physical education, sports and health Teachers, the use of E-Book Flip PDF is effective for use, which is 90%. The conclusion of this community service activity is that it has a good impact on Physical education, sports and health teachers in Palembang City because it can be used as a reference in teaching and improving skills in the digital era.